The Influence of High-Power Ion Beams and High-Intensity Short-Pulse Implantation of Ions on the Properties of Ceramic Silicon Carbide; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Pavlov S. K. Sergey Konstantinovich; Remnev G. E. Gennady Efimovich (2016, 2016)
Title screen